حماية الأقلية في شركة المساهمة - حسناوي اسلام (المسيلة, 2022)
إنّ للأقلية المساهمة في شركة المساهمة مركز هام ودور فعّال في حياة الشركة والمقصود بالأقلية هو امتلاك هذه الفئة النسبة الضئيلة من الأسهم، أمّا الأغلبية يذهب مفهومها إلى امتلاك هذه الفئة أغلبية رأس المال وإنّ سلطة اتّخاذ القرار في شركة المساهمة يتم وفقاً لقانون الأغلبية، إلا أنّ هذا الأخير قد يحيد عن الهدف الذي وضع من أجله بصدور قرارات مشوبة بالتعسف تكون مخالفة لما يقتضيه مبدأ المساواة. ولحماية الأقلية رصدت مختلف التشريعات مجموعة من الوسائل والآليات لحمايتها، منها الحماية القانونية التي تتمثل في ممارسة حقوق أقلية المساهمين داخل وخارج الجمعية العامة وفرض الرقابة على أمور الشركة، بالإضافة إلى الحماية القضائية التي من خلالها يحق للمساهم برفع دعوى المسؤولية بصفته الفردية أو بصفته شريكا فيها، وبالتالي الحفاظ على مصلحته ومصلحة الشركة. الكلمات المفتاحية: شركة المساهمة، أقلية، أغلبية، الحماية القانونية، الحماية القضائية. Abstract: The minority shareholding in the joint stock company has an important position and an active role in the life of the company, and what is meant by the minority is that this category owns a small percentage of the shares, while the majority concept goes to this category owning the majority of the capital, and the decision-making authority in a company. The contribution is made according to the law of the majority, but the latter may deviate from the goal set from him, by issuing obituary decisions that are in violation of what is required by principle of equality. in order to protect the minority, various legislations have monitored a number of means and mechanisms to protect it, including the legal protection represented in exercising the rights of minority shareholders within the and outside the general assembly and imposing control over the company's affairs, in addition to protection jurisdiction through which the shareholder has the right to fill liability claim in his individual capacity or as a partner in it, thus preserving his interest of the company. Key words:joint stock company, minority, majority, arbitrariness, legal protection, judicial protection.
Keywords: : شركة المساهمة، أقلية، أغلبية، الحماية القانونية، الحماية القضائية